DETERMINANTS OF CUSTOMER INTEREST TO SAVING IN SHARIA BANK - Mulyani, Sri; Patriani, Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aims to determine how income, product, and religious factors affect students at an Islamic boarding school (IBS) in Jabung District's desire to banking (saving) with Islamic banks. 2,207 students made up the study's population, while 96 students made up the sample. The results of the study show that religion value on bank products has no significance impact on the student’s intention to banking (saving) with Islamic banks. Meanwhile, the income variable has a significant and positive effect on students' interest to banking (saving) with Islamic banks. Likewise, product information has a significant and positive impact on students' desire to save at Islamic financial institutions. The suggested implication is to increase the interest on saving, Islamic banks need to improve their promotions related to product information so that the number of Islamic bank customers can increase. In addition, it was found that religiosity label on bank products didn’t affect the desire to use Islamic banks. This is because due to the lack of understanding about Islamic banking. So it’s suggested that Islamic banks need to increase socialization and provide more detailed information to students so that students' understanding of Islamic banks can be more intact so that in the end they can be interested in saving in Islamic banks.